Men's knowledge and involvement on obstetric danger signs, birth preparedness and complication readiness in Burayu town, Oromia region, Ethiopia - Addisu Gize; Alemtsehay Eyassu; Balkachew Nigatu; Mekonen Eshete; Nebiyou Wendwessen (BMC, 2019)
Abstract Background Men's involvement in obstetrics care is an important strategy in reducing preventable maternal morbidity and mortality. This is particularly important in developing countries where men often make decision on financial, health and other family issues. Hence, the objective of this study was to assess men's knowledge and involvement in obstetric danger signs; birth preparedness and complication readiness in Burayu town administration, Oromia, Ethiopia. Methods A community based cross-sectional study was conducted in Burayu town administration, Oromia Region from May 2016 to July 2016. Multistage with systematic random sampling techniques were employed. Bivariate and multivariate logistic regression analyses were performed using SPSS version 20. P-value less than 0.05 were taken as a cutoff point to declare significant association. Result A total of 523 men were involved in the study. The mean and ± SD age of the study participant was 36.6 ± 7 years. Majority of the participants were Orthodox religion followers and, employees of private organization, regarding residency majority were residing in urban setting. Pregnancy related vaginal bleeding was the most familiar danger sign recognized by the study participants which was 342(65.4%). From the total, 441(84.3%) of men were highly involved in preparation of arranging for postpartum cultural food expenses, 345(66.0%) for clean clothes both for the baby and mother; and 71-76% participants were involved in availing transport money for antenatal, delivery and postnatal care. The study revealed that educational status of men, monthly income, knowledge of pregnancy danger sign, delivery and post-delivery care, and knowledge of birth preparedness and complication readiness (BP/CR) were significantly associated with men's involvement in BP/CR. Conclusion Majority of participants had knowledge on obstetric danger sign. Men showed low interest to donate blood to their wives during antenatal, delivery and postpartum care. There is a need continued awareness creation on danger sings as well as birth preparedness.